Functional Analysis of the Collagen Binding Proteins of Streptococcus parasanguinis FW213 - Chen, Yi-Ywan M. (mSphere, 2020)
Streptococcus parasanguinis is a dominant isolate of dental plaque and an opportunistic pathogen associated with subacute endocarditis. As the expression of collagen binding proteins (CBPs) could promote the establishment of S. parasanguinis in the host, the functions of three putative CBP-encoding loci, Spaf_0420, Spaf_1570, and Spaf_1573, were analyzed using isogenic mutant strains. It was revealed that S. parasanguinis FW213 bound effectively to fibronectin and type I collagen, but the strain’s affinity for laminin and type IV collagen was quite low. By using various deletion derivatives, it was found that these three loci mediated the binding of S. parasanguinis to multiple extracellular matrix molecules, with type I collagen as the common substrate. Derivative strains with a deletion in any of the three loci expressed reduced binding to trypsin-treated swine heart valves. The deletion of these loci also reduced the viable count of S. parasanguinis bacteria within macrophages, especially the loss of Spaf_0420, but only strains with deletions in Spaf_0420 and Spaf_1570 expressed reduced virulence in the Galleria mellonella larva model. The deletion of Spaf_1570 and Spaf_1573 affected mainly the structure, but not the overall mass, of biofilm cultures in a flow cell system. Thus, CBPs are likely to be more critical for the initial colonization of S. parasanguinis on host tissues during the development of endocarditis. IMPORTANCE Bacteria generally can utilize multiple adhesins to establish themselves in the host. We found that Streptococcus parasanguinis, a dominant oral commensal and an opportunistic pathogen for subacute endocarditis, possesses at least three collagen-binding proteins that enable S. parasanguinis to successfully colonize damaged heart tissues and escape innate immune clearance. The binding specificities of these three proteins for extracellular matrix molecules differ, although all three proteins participate in biofilm formation by S. parasanguinis. The “multiligand for multisubstrate” feature of these adhesins may explain the high adaptability of this microbe to different tissue sites.